Enabling an Inorganic-Rich Interface via Cationic Surfactant for High-Performance Lithium Metal Batteries - Sun, Zejun; Yang, Jinlin; Xu, Hongfei; Jiang, Chonglai; Niu, Yuxiang; Lian, Xu; Liu, Yuan; Su, Ruiqi; Liu, Dayu; Long, Yu; Wang, Meng; Mao, Jingyu; et al. (Nano-Micro Letters, 2024)
An anion-rich electric double layer (EDL) region is favorable for fabricating an inorganic-rich solid–electrolyte interphase (SEI) towards stable lithium metal anode in ester electrolyte. Herein, cetyltrimethylammonium bromide (CTAB), a cationic surfactant, is adopted to draw more anions into EDL by ionic interactions that shield the repelling force on anions during lithium plating. In situ electrochemical surface-enhanced Raman spectroscopy results combined with molecular dynamics simulations validate the enrichment of NO3−/FSI− anions in the EDL region due to the positively charged CTA+. In-depth analysis of SEI structure by X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectrometry results confirmed the formation of the inorganic-rich SEI, which helps improve the kinetics of Li+ transfer, lower the charge transfer activation energy, and homogenize Li deposition. As a result, the Li||Li symmetric cell in the designed electrolyte displays a prolongated cycling time from 500 to 1300 h compared to that in the blank electrolyte at 0.5 mA cm−2 with a capacity of 1 mAh cm−2. Moreover, Li||LiFePO4 and Li||LiCoO2 with a high cathode mass loading of > 10 mg cm−2 can be stably cycled over 180 cycles. Highlights: 1 Cetyltrimethylammonium cations can shield the repelling force on anions to attract more anions into electric double layer region during lithium plating process, facilitating the formation of inorganic-rich solid-state electrolyte interphase (SEI). 2 An inorganic-rich (N/F-containing species) structure of SEI can be evidenced by the in-depth analysis. 3 The cycling lifetime of Li||Li symmetric cell in the designed electrolyte can be extended from 500 to 1300 h. Moreover, full cells with a high cathode mass loading of >10 mg cm-2 can be stably cycled over 180 cycles.